How SAPLING’s herd health innovations have improved pig productivity in Uganda: Pig value chain - Oba, Peter; Hasahya, Emmanuel; Businge, Martha; Dione, Michel M.; Kyobe, Francis; Wairagala, Pamela; Kiryabwire, David; Ahumuza, Ronnie; Marunga, Caroline; Achandi, Esther; Nsadha, Zachary; Namatovu, Jane; et al. (International Livestock Research Institute, 2024)
In Uganda, pig production plays a crucial role in the livelihoods of rural communities, contributing significantly to both food security and income generation. However, significant constraints remain in the value chain, contributing to low production and poor productivity with associated economic losses to farmers. To address these constraints, the International Livestock Research Institute (ILRI) designed and implemented a CGIAR initiative “Sustainable Animal Productivity for Livelihoods, Nutrition and Gender inclusion” (SAPLING). SAPLING’s primary objective is to improve pig productivity, incomes and empower pig farmers in pig production and other value chain actors in pig related businesses in Uganda.